HISTORICAL PERSONAUTY OF JA'FAR AL-SADIQ - Atalan, Mehmet (Fırat University, 2011)
Ja'far al-Sadiq who is the 6th imam in the Shi'ite Imamiyyah seems as an important figure in the early years of the second century when Abbasid received the dynasty from the Umeyye. The works mention Ja'far al-Sadiq's studies. Same nıysterious sciences as astrology, cefr, augury, talisman, chenıistry, magic, and extra ordinary abilities have been referred to Ja'far al-Sadiq. He has been well-known for his scientific personality more than his political identity. He has not taken any part of the Shiite ·rebels as he has not participated in any re bel in his period. He has been taught by many respected ulema(doctors of Islam Theology) and has also trained a lot of respected ulema Tradition of the prophet have agreed on his being a reliable and trustworty narrator. Shiite parties have wanted to gain legality for themselves by imputing their erroneus views to Ja'far al-Sadiq. Because he has been an Imam agreed on by alliance by every body. Ja'far al-Sadiq has been for away from such expressions as divinity, prophethood miracle, bed'a, rec'at, metempsychosis, reincamation, comparison defended by gulat groups, and has pronounced a formal aneiliama against the people talking nonsense and persecuted theirs leaders.
HISTORICAL PERSONAUTY OF JA'FAR AL-SADIQ
Keywords: Religious Studies; Din Araştırmaları